Exercise-induced bronchoconstriction and exercise-induced respiratory symptoms in nurses - Jordan Minov; Jovanka Karadzinska-Bislimovska; Kristin Vasilevska; Risteska-Kuc, Snezana; Saso Stoleski; Dragan Mijakoski (Hindawi Limited, 2011)
In order to assess prevalence and characteristics of exercise-induced respiratory symptoms (EIRSs) and exercise-induced bronchoconstriction (EIB) in health care workers, we performed a cross-sectional study including 48 female nurses from primary care settings and an equal number of female office workers studied as a control group. The evaluation of examined groups included completion of a questionnaire, skin prick tests to common inhalant allergens, spirometry, and exercise and histamine challenge. We found a similar prevalence of EIRSs and EIB in both groups. EIB was closely related to asthma, atopy, family history of asthma, and positive histamine challenge in either group, while the association between EIB and daily smoking in nurses was of borderline statistical significance. Bronchial reaction to exercise was significantly higher in nurses than in controls with EIB. With the exception of exercise induced wheezing, EIRSs were weakly associated with EIB in both groups with a large proportion of false positive results.